Transcendental epoché and the problem of the transformation of ego - Wesołowska, Agnieszka (Folia Philosophica, 2012)
The paper discusses phenomenological reduction as the transformation of ego. Possibility of overcoming natural-objective attitudes leading to revealing of what is the first from which everything that is immediately given takes its sense, is what Husserl calls phenomenological reduction (epoché). This overcoming, which causes a movement from natural attitude to more primal orientation in the genetic sense (meaning transcendental attitude), reveals the transcendental aspect of ego. Acknowledging the primacy of ego over other spheres of being, Husserl rehabilitates the value of subjectivity as transcendental sphere. For it shows that from transcendental point of view it is something more than the change of attitude. Exclusion from the world with reduction leads to revealing its transcendental reverse seen from the perspective of the transformed ego, the ego which acknowledges its constitutive life. With the change in the attitude the peculiar transformation change of ego follows, so that ego in the transcendental-phenomenological attitude becomes unprejudiced spectator of their own intentional (consciousness’) life.